Issues and options for government intervention in the market for terrorism insurance - Dixon, Lloyd S.; Arlington, John.; Carroll, Stephen J., 1940-; Lakdawalla, Darius; Reville, Robert T.; Adamson, David M.; Center for Terrorism Risk Management Policy; Institute for Civil Justice (U.S.); Rand Corporation (Santa Monica, CA : RAND, 2004)
Following the 9/11 terrorist attacks, the federal government adopted the Terrorism Risk Insurance Act (TRIA), which requires insurers to make terrorism coverage available to commercial policyholders. In exchange, the federal government will reimburse insurers for a portion of insured losses above a particular threshold. This paper frames the central issues in the debate over whether to extend, modify, or end TRIA, and explores the role of disaster insurance within a system for managing risks created by the possibility of terrorist attacks and compensating losses caused by those attacks.
Introduction -- Goals for a Risk-Management and Compensation System for Terrorism-Related Losses -- Key Issues in the Debate over TRIA and the Role of Insurance in a Terrorism Risk- Management and Compensation System -- Options -- Conclusions -- Appendix. Background on the Terrorism Risk Insurance Act of 2002.
"RAND Center for Terrorism Risk Management Policy."
Includes bibliographical references (p. 35-37).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: United States; Financial reinsurance -- United States; Risk (Insurance) -- United States; Terrorism insurance -- United States; Terrorism -- Economic aspects -- United States